Impact of Kickxia elatine In Vitro-Derived Stem Cells on the Biophysical Properties of Facial Skin: A Placebo-Controlled Trial - Anastasia Aliesa Hermosaningtyas; Anna Kroma-Szal; Justyna Gornowicz-Porowska; Maria Urbanska; Anna Budzianowska; Małgorzata Kikowska (Applied Sciences)
The growing demand for natural and sustainable skincare products has driven interest in plant-based active ingredients, especially from in vitro cultures. This placebo-controlled study investigated the impact of a facial cream containing 2% Kickxia elatine (L.) Dumort cell suspension culture extract on various skin biophysical parameters. The cream was applied to the cheek once daily for six weeks on 40 healthy female volunteers between the ages of 40 to 49. The evaluated skin parameters including skin hydration, transepidermal water loss (TEWL), erythema intensity (EI), melanin intensity (MI), skin surface pH, and skin structure, wrinkle depth, vascular lesions, and vascular discolouration. The results indicated that significant improvements were observed in skin hydration (from 40.36 to 63.00 AU, p < 0.001) and there was a decrease in TEWL score (14.82 to 11.76 g/h/m2, p < 0.001), while the skin surface pH was maintained (14.82 to 11.76 g/h/m2, p < 0.001). Moreover, the K. elatine cell extract significantly improved skin structure values (9.23 to 8.50, p = 0.028), reduced vascular lesions (2.72 to 1.54 mm2, p = 0.011), and lowered skin discolouration (20.98% to 14.84%, p < 0.001), indicating its moisturising, protective, brightening, and soothing properties. These findings support the potential use of K. elatine cell extract in dermocosmetic formulations targeting dry, sensitive, or ageing skin.